2005
DOI: 10.2131/jts.30.s135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Two-Generation Reproduction Toxicity Study Adding Endopoints to Detect Endocrine Disrupting Activity Using Lindane

Abstract: -A two-generation reproduction toxicity study in rats adding extra endpoints to detect endocrine disrupting activity was conducted using lindane by dietary administration at 0, 10, 60, and 300 ppm, for investigation of its utility. The extra endpoints included anogenital distance (AGD), nipple development, sexual maturation (vaginal opening and preputial separation), estrous cycle, spermatogenesis, sex organ weights, and blood hormone concentrations (thyroid and sex hormones). F1 offspring were examined for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…The 60 ppm group consumed 3.389 ± 0.167 and 8.941 ± 0.677, while the 300 ppm lindane group consumed 16.55 ± 0.95 and 45.21 ± 3.54 mg/kg body weight per day during the gestational and lactational periods, respectively. Lack of retrieval behaviour and consequential litter loss were observed in one 300 ppm lindane-exposed dam [90]. Other than the one case, lindane exposure did not affect any maternal behaviours, including lactation, nest building, and cannibalism [90].…”
Section: Maternal Behaviourmentioning
confidence: 79%
See 1 more Smart Citation
“…The 60 ppm group consumed 3.389 ± 0.167 and 8.941 ± 0.677, while the 300 ppm lindane group consumed 16.55 ± 0.95 and 45.21 ± 3.54 mg/kg body weight per day during the gestational and lactational periods, respectively. Lack of retrieval behaviour and consequential litter loss were observed in one 300 ppm lindane-exposed dam [90]. Other than the one case, lindane exposure did not affect any maternal behaviours, including lactation, nest building, and cannibalism [90].…”
Section: Maternal Behaviourmentioning
confidence: 79%
“…Lack of retrieval behaviour and consequential litter loss were observed in one 300 ppm lindane-exposed dam [90]. Other than the one case, lindane exposure did not affect any maternal behaviours, including lactation, nest building, and cannibalism [90].…”
Section: Maternal Behaviourmentioning
confidence: 79%
“…The eff ect may be relevant, persisting up to the sexual maturation. Although with substantially diff erent study designs, previous results also suggested eff ects of LIN on CYP ontogeny (Matsuura et al, 2005;Johri et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…General toxicological effects (i.e., reduced gains in body weight, decreased food consumption, and deaths of females from the 15 mg/kg/day group) were seen in parental animals [44]. In the two-generation study, Crj:CD(SD)IGS rats (SPF) received 0, 10, 60, or 300 ppm of 99.5% pure g-HCH (corresponding to a dose of 0, 0.5, 3.0, and 15 mg/kg/day, respectively).…”
Section: Mammalian Oral Toxicity: Othermentioning
confidence: 99%